EFFECTIVENESS OF THERAPEUTIC COMMUNICATION TO THE ANXIETY OF PATIENT WITH CHEMOTERAPHY OF NASOPHARING CANCER IN CHEMOTERAPHY OF NASOPHARING CANCER IN CHEMOTHERAPY ROOM OF RSUD Dr. PIRNGADI MEDAN OF 2016 - Silalahi, Elny Lorensi; Sidabutar, Asmi Naomi (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2016)
Anxiety occurred when patient dealing directly to the threat of health and prosperity. Chemotherapy is classification of medical therapy that cause anxiety because there is threat on the physics and spiritual integrity of anyone. The anxiety is caused by fear, frustration, conflict or general respond to the pressure and unfamiliarity (the lack of information/communication from the nurse). The formulation of problem : is there effectiveness of therapeutic communication to the anxiety level of patient in take of NPC chemotherapy in chemotherapy room of RSUD Dr. Pirngadi Medan of 2016. The objective of this research is to study effectiveness of therapeutic communication to the anxiety level to the patient with NPC chemotherapy at RSUD Dr. Pirngadi Medan in 2016. This research is Quasy Experimental with one group Pretest-Posttest design in which on this design there is pretest, before comunication and posttest after communication and observed by questionnaire. The sample procedure in this research is accidental sampling. Based on result of research it indicates that majority after the therapeutic communication, the data without anxiety is 6 persons (60%) and the mild anxiety for 3 persons (30%) and medium anxiety for 1 person (10%).